Molecular dynamics simulation dataset of a microtubule ring in electric field - Průša, Jiří; Ayoub, Ahmed T; Cifra, Michal (Data in brief, 2021)
We present molecular dynamics (MD) trajectories of a single ring of B-lattice microtubule ring consisting of 13 tubulin heterodimers. The data contain trajectories of this molecular system ran under various conditions (two temperature values, three ionic strength values, three values of electric field (including no field), and four electric field orientations). Our data enable us to analyze the effects of the electric field on microtubule under a variety of conditions. This data set was a basis of our in silico discovery, which demonstrates that the electric field can open microtubule lattice [1].
Keywords: Microtubule; Molecular dynamics; Electric field; Biomolecules; Proteins